2022
DOI: 10.1007/s00705-022-05688-0
|View full text |Cite
|
Sign up to set email alerts
|

Hepeliviruses in two waterbodies in Berlin, Germany

Abstract: The order Hepelivirales comprises RNA viruses of four families (Alphatetraviridae, Benyviridae, Hepeviridae, and Matonaviridae). Sequencing of virus genomes from water samples from the Havel River and the Teltow Canal (Teltowkanal) in Berlin, Germany, revealed 25 almost complete and 68 partial genomes of viruses presumably belonging to the order Hepelivirales. Only one of these viruses exhibited a relationship to a known member of this order. The members of one virus clade have a polymerase with a permuted ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Along both waterbodies, green areas and horticulture may further influence the virome composition of soil and water. Whereas human pathogenic viruses such as enteroviruses, noroviruses, adenoviruses, and hepatitis E viruses are detectable with sensitive PCR protocols only at low levels [53], our previous studies gave no indication of the presence of such viruses in our metagenomes but revealed numerous novel picorna-like viruses and hepeliviruses [27,28]. In the present study, we focused on plant-associated viruses and were able to identify 647 viruses related to 10 of the 30 virus families or floating genera known to comprise plant-infecting viruses.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Along both waterbodies, green areas and horticulture may further influence the virome composition of soil and water. Whereas human pathogenic viruses such as enteroviruses, noroviruses, adenoviruses, and hepatitis E viruses are detectable with sensitive PCR protocols only at low levels [53], our previous studies gave no indication of the presence of such viruses in our metagenomes but revealed numerous novel picorna-like viruses and hepeliviruses [27,28]. In the present study, we focused on plant-associated viruses and were able to identify 647 viruses related to 10 of the 30 virus families or floating genera known to comprise plant-infecting viruses.…”
Section: Discussionmentioning
confidence: 56%
“…In order to investigate the virome of two riverine freshwater bodies influenced by human activities, we sequenced RNA extracted from water samples of the Teltow Canal and Havel River in Berlin, Germany. The diversity of picorna-like and hepe-like viruses in these waterbodies has been published previously [27,28]. Here, we describe hundreds of novel viruses presumably associated with plant hosts or related to plant viruses.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The viruses in this study were enriched from a 50 L water sample (sample ID collected in Berlin, Bäkebrücke (site coordinates: 52°26′03″ N, 13°18′57″ E), on 18 July 2017. Details of the enrichment procedure were described previously [8,16,17]. Briefly, five 10 L aliquots were vigorously stirred for 20 min, and the pH was adjusted from 8.1 to 3.5.…”
Section: Sample Collection and Workupmentioning
confidence: 99%
“…The majority of metagenomic studies, however, focused on marine ecosystems, while the viromes of freshwater bodies remained underexplored [12][13][14][15]. In order to understand the virus diversity detected in two German rivers, we analyzed the RNA viromes of the Havel River and the Teltow Canal in Berlin and published partial results [8,16,17]. Here, we present the sequences of more than 500 PLVs detected in the Teltow Canal (named TC-PLVs), many of which are novel, with little similarity to known members of the Picornavirales.…”
Section: Introductionmentioning
confidence: 99%